Sunflower oil seeds in nursery pig diets - G E Fitzner; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1988)
Two hundred forty pigs were used to evaluate the use of various amounts (0, 10, 15, 20, 25%) of black sunflower oil seeds in weanling pig diets. After 14 days, no significant differences were found between any of the dietary treatments in feed intake (FI), average daily gain (ADG), or feed efficiency (F/G). At the conclusion of the 5-wk study, no differences were found in FI, ADG, or F/G between those dietary treatments containing 0, 10, and 15% sunflower seeds. However, in those diets containing 20 and 25% sunflower seeds, there were linear (p<.05) reductions in FI and ADG. These results indicate that sunflower seeds, when finely ground using a hammermill with a 1/8 in screen, can be used in diets for weanling pigs up to 15% of the diet with no reduction in performance.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Nursery pigs; Sunflower seeds; Weanling pigs; Starter diets